Procalcitonin and Interleukin-6 in pediatric patients admitted with suspected sepsis at Tertiary Care Hospital - Temboonnark, Panipak; Klaiklueng, Kittipol; Karoonboonyanan, Wissaroot; Ratanamongkol, Panjachat (Chulalongkorn Medical Journal, 2023)
Background : Bacterial sepsis remains one of the leading causes of mortality and morbidity among children. Early identification of individuals at risk of developing life-threatening sepsis could enable early treatment and improve outcomes. Procalcitonin (PCT), the peptide hormone precursor of calcitonin, and Interleukin-6 (IL-6), the pro-inflammatory cytokine, are both substances that present in higher concentrations after inflammation. The potential value of measuring PCT and IL-6 levels are recognized as biological markers in pediatric patients with systemic inflammatory response syndrome (SIRS) in both early diagnosis of sepsis and to differentiate sepsis from the other SIRS non-septic conditions, has higher accuracy than the routine laboratory tests pragmatically such as total leukocytes count and C-reactive protein (CRP). Objectives : To define the clinical and laboratory predictive factors for early diagnosis in pediatric bacterial sepsis and distinguishing from the other SIRS non-septic conditions, including the development of the risk scoring system for pediatric bacterial sepsis prediction. Methods : The diagnostic prediction research was designed from the prospective data from September 2015 to June 2016 at the Department of Pediatrics, Bhumibol Adulyadej Hospital, Bangkok, Thailand. Forty-nine patients from the age of 1 month to 15 years old who met the criteria of SIRS definition were recruited into the study. Multivariable logistic regression was performed to select the strongest predictors then transformed to develop the final bacterial sepsis score (FBAC score). Results : The best clinical and laboratory predictors included female gender, PCT, IL-6, CRP levels prior to treatment on admission date and CRP level at 24 hours after starting of the treatment. The developed FBAC score predicted bacterial sepsis correctly with an AuROC of 86.5%. The patients who have FBAC scores below 10 (low risk category) will have the chance to be bacterial sepsis 10 times less (likelihood ratio of positive; LHR + 0.1, P - value 0.01) and the potential bacterial septic patients will have more than 6 times increasingly (LHR+ 6.13, P - value 0.02) if their total FBAC scores are higher than 30 (high risk category). Conclusions : The developed FBAC scores will help pediatricians to predict bacterial sepsis for early treatment intervention and can distinguish bacterial sepsis from the other SIRS non-septic conditions.